2022
DOI: 10.1007/s10531-022-02423-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining diversity of terrestrial mammal communities across forest reserves in Sabah, Borneo

Abstract: Tropical forest reserves have conservation value for terrestrial mammals and are threatened by anthropogenic pressures, especially conversion to other land-use types. To assess mammalian biodiversity of forest reserves in Sabah, Borneo, we used camera trapping data to estimate species richness, beta diversity, phylogenetic and functional diversity in nine forest reserves with different management classifications and backgrounds. Multiregional multispecies occupancy models (MSOM) were used to differentiate spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Previous research indicates that RIL has less impact on forest structure compared to conventional logging methods (Zarin et al 2007, Putz et al 2008, and subsequently maintains higher biodiversity (Bicknell et al 2014, Bohnett et al 2022. Additionally, the preservation of 30-m riparian buffers throughout the reserve potentially reduces the negative impacts of logging on sensitive aquatic habitats (Asad et al 2021a(Asad et al 2022.…”
Section: Freshwater Turtle Responses To Rilmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that RIL has less impact on forest structure compared to conventional logging methods (Zarin et al 2007, Putz et al 2008, and subsequently maintains higher biodiversity (Bicknell et al 2014, Bohnett et al 2022. Additionally, the preservation of 30-m riparian buffers throughout the reserve potentially reduces the negative impacts of logging on sensitive aquatic habitats (Asad et al 2021a(Asad et al 2022.…”
Section: Freshwater Turtle Responses To Rilmentioning
confidence: 99%
“…These methods result in 50% less damage to remnant forests, thus maintaining watersheds while reducing sedimentation and riparian habitat disturbance (Pinard et al 1995, Sabah Forestry Department 2024). As such, RIL‐managed forests maintain higher biodiversity compared to conventionally logged sites (Bicknell et al 2014, Brozovic et al 2018, Bohnett et al 2022). While responses of various taxa to RIL practices are documented (amphibians, Asad et al 2021 a ; mammals, Brozovic et al 2018, Guharajan et al 2021, Bohnett et al 2022; birds, Edwards et al 2012), the impact of RIL on Southeast Asia's freshwater turtles remains unstudied but should prove valuable for informing future conservation measures (Cox et al 2022).…”
mentioning
confidence: 99%
“…Numerous scientific studies have demonstrated that CFs can enhance forest conditions through sustainable forest management [22][23][24][25][26][27][28][29][30] and have found that household-level income from CFs is sustainable [31]. Recently, there have been sustainability assessments conducted among CFUGS in Nepal, including the 3L causative-benchmarking model that can help assess how well the CFs can meet performance targets by evaluating how three "layers" of public-policy goals, socioeconomic theories, and criteria and indicators interact [8].…”
Section: Introductionmentioning
confidence: 99%
“…As of 2010, The Southeast Asian island of Borneo had already lost about half of its tropical forest cover; of the remaining forest, only 53.8% was classified as intact forest; however, 42% of this forest fell within areas designated for production (Gaveau et al, 2014 ). Studies assessing the impact of different logging regimes on biodiversity in Borneo largely showed that many species persist in logged landscapes particularly if managed sustainably (Bohnett et al, 2022 ; Brodie et al, 2015 ; Meijaard et al, 2005 ; Sollmann et al, 2017 ; Wong & Linkie, 2013 ). At the same time, large areas of Borneo have already been rapidly converted to industrial tree plantations (Chan, 1998 ; McShea et al, 2009 ; Rautner, 2005 ; Reynolds et al, 2011 ) and further expansion is expected (Gaveau et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing the impact of different logging regimes on biodiversity in Borneo largely showed that many species persist in logged landscapes particularly if managed sustainably (Bohnett et al, 2022;Brodie et al, 2015;Meijaard et al, 2005;Sollmann et al, 2017;Wong & Linkie, 2013). At the same time, large areas of Borneo have already been rapidly converted to industrial tree plantations (Chan, 1998;McShea et al, 2009;Rautner, 2005;Reynolds et al, 2011) and further expansion is expected (Gaveau et al, 2016).…”
Section: Introductionmentioning
confidence: 99%